ARTIFICIAL INTELLIGENCE IN HISTOLOGY: DIGITAL ANALYSIS AND AUTOMATION IN DIAGNOSTICS - Fazliddin Arzikulov; Komiljonov Azizbek (Modern American Journals, 2025)
In recent years, the application of artificial intelligence (AI) and digital technologies in medicine, particularly in histology, has radically transformed the diagnostic process. This article comprehensively highlights the role of AI in automatic analysis of histological images, cell segmentation, tumor detection, and early diagnosis of diseases. The advantages of digital pathology and machine learning technologies in clinical diagnostics, their contribution to reducing errors, and increasing efficiency are analyzed.
Keywords: Artificial intelligence, digital pathology, machine learning, histological image, diagnostics, automation, segmentation.